Impacts of the CSR strategies of technology companies on performance and competitiveness - Juan Andrés Bernal-Conesa; Antonio Juan Briones-Peñalver; Carmen de Nieves-Niet (Tourism & Management Studies)
This study used structural equation modelling to analyse and investigate the adoption of corporate social responsibility (CSR) strategies by the Spanish technology industry and the impacts of these strategies on technology companies’ performance and competitiveness. The research was conducted using a survey of companies located in Spanish science and technology parks. The analyses’ results reveal positive, direct and statistically significant relationships between companies’ CSR strategies and competitiveness and between their competitiveness and performance. In addition, the results show that competitiveness is a mediating variable in the relationship between CSR strategies and technology companies’ performance.